Evaluation of Sensory Attributes of Soft Candy Using Taro Leaf Extract as Influenced by Variations of Gelatin and Glucose Syrup - Maharani, Regita Suci; Arzani, Lalu Danu Prima (Universitas Bumigora, 2024)
Although taro is widely grown in Indonesia, it is one of the underutilized crops which is a good source of nutrition. one part of taro that is rarely utilized is the leaves. The objective of this research is to determine the effect of glucose syrup and gelatin concentrations on the organoleptic properties (preference for color, taste, and texture) of soft candy made from taro leaf extract. The method used in this research is experimental which is arranged in a Completely Randomized Factorial Design (CRD) with two factors, which are The concentrations of are (25%, 35%, 45%) and the concentrations of gelatin are (20%, 25%, 30%). Each treatment being repeated three times. The obtained data were analyzed using ANOVA (analysis of variance), and Duncan’s test was conducted if significant differences were obtained. The results shows that soft candy with 35% glucose syrup and 25% gelatin had the highest preference for color. The formulation with 35% glucose syrup and 30% gelatin was most preferred for aroma. The formulation with 45% glucose syrup and 30% gelatin received the highest scores for texture (3.90±0.308) and flavor (3.95±0.63). This research demonstrates that optimizing glucose syrup and gelatin concentrations in soft candies made from underutilized taro leaf extract can significantly enhance specific sensory attributes like texture and flavor. This study can contribute in providing valuable insights for future product development and highlighting the potential of taro leaves as a valuable food ingredient.